Investigation into FHA Multiple Dwelling Projects: hearings before the United States Senate Committee on Government Operations, Permanent Subcommittee on Investigations, Eighty-Ninth Congress, second session, on Aug. 24, 25, 30, 1966. - United States. (U.S. G.P.O., 1966)
Reviews default rate on FHA guaranteed apartment mortgages and FHA loan management practices. Investigates alleged mismanagement involving the Barrington Plaza project in Los Angeles.
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VIII
Reviews default rate on FHA guaranteed apartment mortgages and FHA loan management practices. Investigates alleged mismanagement involving the Barrington Plaza project in Los Angeles.